Associations between suicide attempts and clinical, metabolic, and inflammatory markers in Chinese patients with long-term schizophrenia - Zhao, Lili; Liu, Lewei; Zhang, Xu; Zhang, Xi; Yao, Xianhu; Li, Wenzheng; Xia, Lei; Liu, Huanzhong (Frontiers in Psychiatry, 2025)
BackgroundSuicide attempt (SA) is common among patients with long-term schizophrenia (SCZ), but the mechanisms underlying its occurrence remain incompletely understood. Thus, the purpose of this study was to investigate the associations between SA and clinical, metabolic, and inflammatory markers in Chinese patients with SCZ.MethodsThis study enrolled 299 patients with SCZ. SA, psychotic symptoms, depressive symptoms, and insomnia were evaluated through standardized questions, the Positive and Negative Syndrome Scale (PANSS), the Calgary Depression Scale for Schizophrenia (CDSS), and the Insomnia Severity Index (ISI), respectively. In addition, we measured metabolic parameters including total cholesterol (TC), triglycerides (TG), high-density lipoproteins (HDL) and low-density lipoproteins (LDL), fasting blood glucose (FBG), and fasting insulin (FI), along with inflammatory cytokine levels, including interleukin (IL)-1β, IL-6, IL-17A and tumor necrosis factor-α (TNF-α). Univariate analyses (chi-square test, the independent samples t-test or the Mann-Whitney U-test) were followed by multivariable logistic regression (“Forward: LR”) to identify independent risk factors for SA. Log10-transformed values were applied to inflammatory-cytokine data to approximate normal distribution. All analyses were performed in SPSS 23.0; P < 0.05 (two-sided) was considered statistically significant.ResultsThe prevalence of SA in patients with SCZ was 22.7%. Patients in the SA group had a higher proportion of females, more severe depressive symptoms, and higher levels of TC, TG, Log IL-1β, and Log IL-6 (all P < 0.05). Logistic regression analyses showed that gender (OR = 0.239, 95% CI = 0.127 - 0.450, P < 0.001), CDSS total score (OR = 1.250, 95% CI = 1.146 - 1.364, P < 0.001), TC (OR = 1.682, 95% CI = 1.178 - 2.402, P = 0.004), and Log IL-1β (OR = 2.225, 95% CI = 1.114 - 4.564, P = 0.024) were independent correlates of SA.ConclusionsFemale gender, greater depressive severity, and elevated metabolic and proinflammatory markers (specifically TC and IL-1β) were independently associated with increased risk of SA in Chinese patients with long-term SCZ. These findings suggest that future interventions targeting metabolic and inflammatory pathways may hold promise for preventing SA in this population.